Clinical Trials Gone Missing—A Potential Source for Publication Bias in Dentistry - Tomack, Justin; Mascardo, Kathleen; Chen, Chia-Yu; Chen, Tony; Li, Xihao; Kim, David M.; Machtei, Eli E. (Publications (Basel), 2024)
Background: The aim of this study was to examine publication bias associated with a failure to report research results of studies that were initially posted on the ClinicalTrials.gov registry and to examine factors associated with this phenomenon. Methods: A search was conducted in the ClinicalTrials.gov registry using six dental-related topics. Corresponding publications for trials completed between 2016 and 2019 were then searched using PUBMED, EMBASE and Google Scholar. For studies lacking matching publications, we emailed the primary investigator and received some additional data. For included studies, we recorded additional variables: industry funding, site setting (academic, private research facilities or private practice), design (single or multi-center), geographical location and commencement date vis a vis registration and publication dates. Results: A total of 744 entries were found, of which 7 duplicates were removed; an additional 67 entries just recently completed were removed. An additional 7 studies were in different fields and thus removed. Thus, 663 trials were included; of these, only 337 studies (50.8%) were published. The mean registration to publication interval was 29.01 ± 25.7 months, ranging from +142 to −34 months (post factum registration). Less than 1/3 of the studies were posted prior to commencement, of which much smaller proportions were published (37.3%). Studies that were posted after commencement (n = 462) had a much higher publication rate (56.7%), p < 0.001. Multi-center studies and those conducted in commercial facilities had much higher, though non-significant, publication rates (56.5% and 58.3%, respectively). Conclusions: With only half of the studies registered being published, a major source for publication bias is imminent.